2016
DOI: 10.4093/dmj.2016.40.3.230
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vildagliptin and Pioglitazone in Korean Patients with Type 2 Diabetes Inadequately Controlled with Metformin

Abstract: BackgroundWe compared the efficacies of vildagliptin (50 mg twice daily) relative to pioglitazone (15 mg once daily) as an add-on treatment to metformin for reducing glycosylated hemoglobin (HbA1c) levels in Korean patients with type 2 diabetes.MethodsThe present study was a multicenter, randomized, active-controlled investigation comparing the effects of vildagliptin and pioglitazone in Korean patients receiving a stable dose of metformin but exhibiting inadequate glycemic control. Each patient underwent a 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Here, we show an association between rs17574 and the presence of high apoB and non-HDL-C levels. Consistent with the observed association between polymorphisms in the DPP4 gene with apoB and non-HDL-C, pharmacological inhibition of DPP4, has been found associated with lower total cholesterol, apoB, triglycerides, non-HDL-C and VLDL levels [55][56][57].…”
Section: Discussionsupporting
confidence: 67%
“…Here, we show an association between rs17574 and the presence of high apoB and non-HDL-C levels. Consistent with the observed association between polymorphisms in the DPP4 gene with apoB and non-HDL-C, pharmacological inhibition of DPP4, has been found associated with lower total cholesterol, apoB, triglycerides, non-HDL-C and VLDL levels [55][56][57].…”
Section: Discussionsupporting
confidence: 67%
“…Since the first edition was published in 1990, the Clinical Practice Guidelines for adult patients with T2DM have been periodically updated by the Committee of Clinical Practice Guidelines of the KDA [ 1 ]. However, since the fifth edition was published in 2015, many results from large clinical trials of antidiabetic drugs have been introduced, and clinical evidence from studies assessing Korean patients with T2DM who use dipeptidyl peptidase 4 (DPP4) inhibitors, glucagon-like peptide 1 receptor agonists (GLP-1RAs), or sodium-glucose cotransporter 2 (SGLT2) inhibitors have accumulated [ 2 3 4 5 ]. All novel evidence and results were reviewed to extract recommendations for the treatment of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, mean changes in HOMA‐IR from baseline to 24 weeks showed that evoglipitin did not have a statistically significant effect on insulin resistance (−0.17 ± 1.72, P = .1233). In a previous study among Korean T2DM patients, another DPP‐4 inhibitor (vildagliptin) had similar effects when compared to pioglitazone …”
Section: Discussionmentioning
confidence: 90%
“…In a previous study among Korean T2DM patients, another DPP-4 inhibitor (vildagliptin) had similar effects when compared to pioglitazone. 26 We first verified the tolerability and safety of a daily dose of evogliptin 5 mg up to week 52. The incidence of AEs was similar to that with use of sitagliptin, which is one of the most widely prescribed DPP-4 inhibitors.…”
Section: Discussionmentioning
confidence: 98%